Mitstreiter im Volkstumskampf. Deutsche Justiz in den eingegliederten Ostgebieten 1939-1945 - Becker, Maximilian (Quellen und Darstellungen zur Zeitgeschichte, 2014)
In Poland during the Second World War, the German judicial system was part of the National Socialist occupation machine from the outset and became a key element in the policy of Germanization, Germany`s principal objective for the annexed portions of Poland. The courts systematically discriminated against Poles, and between September 1939 and the beginning of 1945, imposed thousands of death sentences.